Tapping The New Horizons In Prenatal Screening: Maternal Blood For Cell Free DNA Detection - Khan, Sikandar Hayat; Hafeez, Ayesha; Afzal, Raja Kamran (Pakistan Armed Forces Medical Journal, 2022)
The data from first trimester abortions, still births and neonatal deaths indicates an alarming prevalence of chromosomal abnormalities.1 Moreover, in a region like subcontinent, where marriages between cousins have prevailed for long and the rate of consanguinity is high, there is a significant prevalence of various genetic disorders. The convention to date in prenatal screening pivots around either high resolution ultrasonographic examination for fetal anomalies, invasive procedures such as amniocentesis or chorionic villus sampling and blood/urine biomarker measurements including unconjugated estriol, Alpha feto protein (AFP) and others. There is, without a shadow of doubt, an emerging need for more sensitive, robust and clinically more yielding early markers with broader coverage of genetic defects in pregnancy. The expansion of diagnostic molecular techniques have made it possible to replace the conventional invasive techniques. Circulating cell free DNA (cfDNA) is a fragmented and slightly denatured DNA fragment (50-280bp) released into circulation after broken cells are shed into the blood circulation subsequent to cellular damage or some denaturing process.5 Advances in nano molecular diagnostics can decipher the tiny signatures on their surfaces, be it some cancerous process or some genetic anomaly from feto-maternal mix up of blood. cfDNA overtime has become detectable to depict the changes in genetic structure of fetal diseases very early in the course of pregnancy.